A Survey of RDA in Asia and a Vision for Future Development. Issue 2 (3rd April 2019) - Dandan, Zhao; Zheng, Ding; Dongfeng, Qi
Abstract: At the end of 2017, the National Library of China (NLC) was invited by the RDA Board to become the National Institution Representative for Asia. It is a good opportunity for the NLC to be more visible and to contribute to the international community. However, RDA promotion is a demanding task considering the economic and professional conditions in Asia. In this article, we (1) summarize RDA study and practice in China especially NLC's advances, (2) analyze the survey of Asian libraries conducted by the NLC in 2018 with regard to RDA, and (3) discuss RDA promotion initiatives undertaken by the NLC.